Training on Utilizing Plastic Spoons to Make Crafts to Boost Community Creativity and Income - Shaleh, Musliha; Nasir, Munawir; Ansar, Nur Annisa; Mulia, Intan (Advances in Community Services Research, 2026)
Purpose: This community service activity aims to improve the knowledge and skills of the Padanglampe Village community, especially the Family Empowerment and Welfare (PKK) group of mothers, in utilizing used plastic spoons to make crafts that are both useful and economically valuable. The program also aims to foster creativity and open up opportunities to increase income through plastic waste processing. Research Design and Methodology: The approach used was a participatory method, in which the community was directly involved in all stages of the activity, from preparation to implementation. The training process included socialization, discussion, question and answer sessions, deliberation, material delivery, and hands-on practice in craft making. Findings and Discussion: Initial interviews showed that most participants still had limited knowledge about creativity and the use of plastic waste as a source of income. Through training, participants gained a new understanding of plastic spoon processing techniques and their economic potential. The enthusiasm of the participants showed a high level of interest in developing creative skills based on plastic waste. Implications: This program has practical implications for increasing community capacity in waste management and creative economic development. This training model can also be used as a reference for community empowerment programs in other regions facing similar problems.